Peers without fears? Barriers to effective communication among primary care physicians and oncologists about diagnostic delays in cancer. Issue 11 (27th June 2017) - Lipitz-Snyderman, Allison; Kale, Minal; Robbins, Laura; Pfister, David; Fortier, Elizabeth; Pocus, Valerie; Chimonas, Susan; Weingart, Saul N
Abstract : Objective: Relatively little attention has been devoted to the role of communication between physicians as a mechanism for individual and organisational learning about diagnostic delays. This study's objective was to elicit physicians' perceptions about and experiences with communication among physicians regarding diagnostic delays in cancer. Design, setting, participants: Qualitative analysis based on seven focus groups. Fifty-one physicians affiliated with three New York-based academic medical centres participated, with six to nine subjects per group. We used content analysis to identify commonalities among primary care physicians and specialists (ie, medical and surgical oncologists). Primary outcome measure: Perceptions and experiences with physician-to-physician communication about delays in cancer diagnosis. Results: Our analysis identified five major themes: openness to communication, benefits of communication, fears about giving and receiving feedback, infrastructure barriers to communication and overcoming barriers to communication. Subjects valued communication about cancer diagnostic delays, but they had many concerns and fears about providing and receiving feedback in practice. Subjects expressed reluctance to communicate if there was insufficient information to attribute responsibility, if it would have no direct benefit or if it would jeopardise their existing relationships. They supported sensitive approaches to conveying information, as they feared eliciting or being subject to feelings of incompetence or shame. Subjects also cited organisational barriers. They offered suggestions that might facilitate communication about delays. Conclusions: Addressing the barriers to communication among physicians about diagnostic delays is needed to promote a culture of learning across specialties and institutions. Supporting open and honest discussions about diagnostic delays may help build safer health systems.